Pengaruh Kepemimpinan Demokratis, Budaya Organisasi Dan Motivasi Kerja Terhadap Organization Citizenship Behavior Pada Pt Diamondfit Garment Indonesia - Sintya Kartika Dewi; Kusuma Chandra Kirana; Didik Subiyanto (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to examine the effect of democratic leadership, organizational culture and work motivation on organizational citizenship behavior. The study took samples at a garment company located in Boyolali Regency, Central Java. This type of research is quantitative research with non-probability sampling method and sampling technique using saturated sample. Data was collected through interviews using a questionnaire. The number of questionnaires that were processed were 62 questionnaires. Data were analyzed using SPSS 23 software. Based on the results of this study, it shows that democratic leadership has an effect on OCB, organizational culture has an effect on OCB, work motivation has an effect on OCB, simultaneously democratic leadership, organizational culture and work motivation have an effect on organizational citizenship behavior. Keywords: Democratic leadership, Organizational culture, Work motivation, Organizational citizenship behavior, OCB